2014
DOI: 10.5194/gmd-7-1001-2014
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transport, emissions and the role of compensating errors in chemical transport models

Abstract: Abstract. The balance between turbulent transport and emissions is a key issue in understanding the formation of O 3 and particulate matter with diameters less than 2.5 µm (PM 2.5 ). Discrepancies between observed and simulated concentrations for these species have, in the past, been ascribed to insufficient turbulent mixing, particularly for atmospherically stable environments. This assumption may be simplisticturbulent mixing deficiencies may explain only part of these discrepancies, and as turbulence param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Overall, the O 3 , NO 2 , CO and prior results for total VOC suggest that the precursor emissions (NO, CO, VOCs) determining the oxidizing capacity of the troposphere (O 3 , OH, NO 3 ) are modelled in AURAMS reasonably well (see Makar et al 2014c for a comparison of AURAMS and CMAQ results).…”
Section: Model Evaluation For Other Pollutants: Ozone Nitrogen Dioximentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, the O 3 , NO 2 , CO and prior results for total VOC suggest that the precursor emissions (NO, CO, VOCs) determining the oxidizing capacity of the troposphere (O 3 , OH, NO 3 ) are modelled in AURAMS reasonably well (see Makar et al 2014c for a comparison of AURAMS and CMAQ results).…”
Section: Model Evaluation For Other Pollutants: Ozone Nitrogen Dioximentioning
confidence: 84%
“…Lower limits to the pollutant vertical diffusivities (0.1 m 2 /s) were included to simulate the sub-grid scale mechanical mixing processes. The relative impact of such lower limits is discussed in detail in Makar et al (2014c).…”
Section: Regional Air Quality Model Descriptionmentioning
confidence: 99%
“…Fine particle concentrations are much more sensitive to the applied emission post-processing technique. We note here, that recent work has pointed out that the sensitivity of modeled concentrations the spatiotemporal resolution of the emission inventory is model-dependent (Makar et al, 2014).…”
Section: Sensitivity To Emission Post-processing (Ann Vs Post)mentioning
confidence: 99%
“…Mailler et al (2013) found that model results are highly sensitive to the coefficients used for the vertical distribution of emissions. Makar et al (2014) investigated the response of modeled concentrations to the refinement of the spatial and temporal allocation of input emissions and found that the model was as sensitive to these improvements as to the vertical mixing parameterization. Also they conclude that the temporal distribution of emissions in particular, could be very important in stable urban atmospheres and that this sensitivity is reduced with increased mixing conditions.…”
Section: Description Of the Sensitivity Simulationsmentioning
confidence: 99%
“…Because gravity waves are ubiquitous in the stable boundary layer, they must always be assumed present and active in the vertical redistribution of kinetic energy and momentum. Atmospheric models usually enforce minimum values for turbulent kinetic energy or momentum diffusivity throughout the vertical domain (Makar et al 2014). …”
Section: Turbulent-flux Parametrizationmentioning
confidence: 99%